Analisis Pertumbuhan Tanaman Tebu (Saccharum officinarum L.) Akibat Aplikasi Vermikompos dan Plant Growth Promoting Rhizobacteria (PGPR) - Muliandari, Nadya; Sudiarso, Sudiarso; Sumarni, Titin (Jurnal Agro Industri Perkebunan, 2021)
Sugarcane (Saccharum officinarum L.) play an important role for sugar consumption in Indonesia. Problem found with sugar industry in Indonesia is the low productivity of sugarcane because of cultivation techniques caused by low soil fertility. This research aimed to determine effect of Plant Growth Promoting Rhizobacteria (PGPR) and vermicompost in increasing the growth of sugarcane. The research method used Randomized Block Design (RBD) consisted of 2 factors with a combination of 6 treatments. The first factor was A1 = without PGPR A2 = PGPR (10 ml.L-1) and the second factor was P1 = 3.5 t.ha-1 (50% vermicompost recommended fertilizer), P2 = 7.t ha-1 (100% vermicompost recommended fertilizer) and P3 = 10.5 t.ha-1 (150% vermicompost recommended fertilizer). Variables of this observation are plant height, number of tillers, number of stems, number of internodes, stem diameter, brix value and the yield of sugarcane. At the age 7 months after planting, the treatment of PGPR application at a vermicompost dose of 7 t.ha-1 (78.46 t.ha-1) was able to reduce the need for a vermicompost dose which was shown by a higher yield value compared to without PGPR application with vermicompost 3.5 t.ha-1 and vermicompost dose of 7 t.ha-1. A higher stem weight obtained in the PGPR treatment when compared to the treatment without PGPR. At a vermicompost 7 t.ha-1 and a vermicompost 10.5 t.ha-1 showed a higher stem weight compared to vermicompost 3.5 t.ha-1.